Generation of Electrical Power by Integrating Horizontal Wind Turbine in to the Spoiler of Electric Car - Harikrishna Mukeshkumar Muniaraj; Srihari S (Journal of Advanced Mechanical Sciences, 2024)
The transportation industry consumes most of the fossil fuel and releases enormous amount of Co2 which leads to global warming. Hence there is always a need for generating green energy for replacing fossil fuel-based transportation. The recent booming of electrical vehicle is considered as alternative but still they are using the power for charging synthesized by burning fossil fuels. If the wind energy of a moving car is used to generate electrical power, then the charging frequency can be reduced and there by indirectly reduce the consumption of fossil fuel. Moreover, the main disadvantage of electric car is frequent charging. If a system to generate power by using wind energy in moving car, it could supplement the power requirement. Hence, we have designed a prototype spoiler integrated with inbuilt turbine and motor to supplement the power requirement by utilizing wind energy of a moving electric car.